On the challenges and constrains of ultra-low emission limits: Formaldehyde oxidation in catalytic sinusoidal-shaped channels. (23rd February 2019) - Torkashvand, Bentolhoda; Maier, Lubow; Hettel, Matthias; Schedlbauer, Thomas; Grunwaldt, Jan-Dierk; Deutschmann, Olaf
Highlights: 3D modelling study of catalytic converters with sinusoidal-shaped channels. Investigation of influence of washcoat distribution on catalyst performance by means of 3D model. Investigation of challenges and constrains concerning upcoming ultra-low emission regulations. Abstract: This paper presents the results of a study on kinetics and mass transfer in a catalytically coated metallic monolith converter with sinusoidal-shape channels. Hereby, experimental and modelling studies are performed on a commercial Pt-based oxidation catalyst for total oxidation of formaldehyde applicable in after-treatment system of lean-burn gas engines. For the description of flow field and mass transport inside the channel as well as species diffusion and chemical reaction inside the porous washcoat, a three-dimensional approach is applied and the calculations are performed, using ANSYS-FLUENT. Three different computational models representing different washcoat distribution are compared. The effects of washcoat distribution and mass transfer on kinetics and catalyst activity are investigated in detail and the numerically obtained results are compared with experimental data. Despite of a very high intrinsic reaction rate at operation temperature, the complete conversion of formaldehyde could not be achieved experimentally. All three models have shown to operate in mass transport limited regime, where the diffusion distance from bulk to catalyst surface as well as reactant concentration play a significant role. Thus, very low levels of formaldehyde emissions are technically hard to achieve and a long catalyst is required to overcome the low diffusion rate due to the small concentration gradient. The computational results indicate also that due to individual structure of each channel of metallic monolith in real applications, they can behave distinctly from each other and one channel does not represent the entire monolith. It is also evident from simulated data that the lack of knowledge of washcoat properties and distribution may bring about misleading results since apparent reaction rates can be highly sensitive to this parameter for particularly catalytic reactions under mass-transfer-controlled conditions.